2017
DOI: 10.1007/s10750-017-3193-4
|View full text |Cite
|
Sign up to set email alerts
|

Does artificial drawdown affect zooplankton structure in shallow lakes? A short-term study in a tropical reservoir

Abstract: Water level fluctuation by artificial drawdown is one management activity that has the potential to control macrophyte growth, but there is little knowledge of how this operational procedure affects other biotic components of the ecosystem. This study investigated zooplankton dynamics in response to artificial drawdown over a short timeframe (13 days) in a Brazilian reservoir, by examining the impact on zooplankton communities in two shallow lakes (Lake Pedra Branca-LPB, and Guaritá-LG) connected to a reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…In contrast, the abundances of cyclopoids and calanoids increased after the water‐level drawdowns. This result is consistent with previous findings in shallow lakes (Chaparro et al, 2011; Havens et al, 2007; Portinho & Nogueira, 2017). Cyclopoids can feed efficiently on cyanobacteria, and by breaking down cyanobacterial colonies and filaments into smaller pieces, they can suppress cyanobacterial blooms (Urrutia‐Cordero et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, the abundances of cyclopoids and calanoids increased after the water‐level drawdowns. This result is consistent with previous findings in shallow lakes (Chaparro et al, 2011; Havens et al, 2007; Portinho & Nogueira, 2017). Cyclopoids can feed efficiently on cyanobacteria, and by breaking down cyanobacterial colonies and filaments into smaller pieces, they can suppress cyanobacterial blooms (Urrutia‐Cordero et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Even in the absence of submerged macrophytes, however, water-level drawdown can modify stratification and mixing regimes, promote reoxygenation of bottom waters (Baldwin et al, 2008;da Costa et al, 2016;Naselli-Flores & Barone, 2005;Noges & Noges, 1999), and reduce the abundance of phytoplankton and cyanobacteria (da Costa et al, 2016;Lehman et al, 2009;Noges et al, 2003;Serruya & Pollingher, 1977;Teferi et al, 2014). It has also been reported that water-level drawdown can increase periphyton abundance and the hatching of cladoceran resting eggs (Chaparro et al, 2011;Noges & Noges, 1999;Portinho & Nogueira, 2017;Rodusky, 2010). These biological changes may indirectly help to improve water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Zooplankton are sensitive to changes in the environment, and their community structure will be affected by changes in water temperature, pH, and other environmental factors. This sensitivity is conducive to the evaluation of environmental water quality, and thus zooplankton are often used as indicators in environmental monitoring [2][3][4][5][6]. In aquatic ecosystems, species are usually identified by traditional morphological methods.…”
Section: Introductionmentioning
confidence: 99%